THE ORIGIN OF THE RELICT WALNUT–APPLE FORESTS OF KYRGYZSTAN AND THE HISTORY OF THE KYRGYZ WALNUT IN THE PRESENT ARSTANBAP REGION (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the results of expeditionary factual studies and literature data on the origin of Kyrgyz walnuts and the wild relict walnut–apple forests of Kyrgyzstan. At present, these forests are considered economically valuable fruit-bearing plants and represent the only large-scale natural massif of this kind in the world. Particularly valuable are the aboriginal, relict, and unique autochthonous forest types, as well as the biological diversity within them, which has no analogues worldwide.
Keywords: Kyrgyzstan, origin, walnut (Juglans regia L.), royal fruit, relict walnut–apple forests, anthropogenic impact, flora, uniqueness, biological diversity, large massif